A roadbed material and method for preparing roadbed material based on coal gangue material
By using coal gangue and other ingredients in the roadbed materials and the coordinated cooperation of stable connection adjusters and modifiers, the problem of insufficient performance of existing coal gangue roadbed materials has been solved, and its compressive, permeable, frost and heat resistance are significantly improved.
Patent Information
- Application Number
- CN202510192090.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The compressive strength, chloride ion permeability, freezing resistance, heat resistance and durability of existing coal gangue roadbed materials limit their use efficiency.
Coal gangue is used as the matrix material, combined with silicate cement, sand and gravel, fly ash and limestone, and the performance of the roadbed material is optimized through stable connection adjustment and modifier based on sheet talc hybrid glass fiber.
It significantly improves the compressive strength and chloride ion permeability of the roadbed materials, and improves the freezing, heat resistance and durability, and improves the efficiency of the product.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of roadbed materials, and in particular to a method for preparing roadbed materials based on coal gangue materials. Background Art
[0002] With the continuous and steady growth of the national economy and the advancement of urbanization, the demand for roadbed materials as one of the basic materials in the construction of transportation infrastructure such as rural and urban roads, mining roads, highways, railways, bridges, etc. is huge. At the same time, with the increasingly stringent environmental protection policies and the higher technical requirements for roadbed quality in my country's transportation environment, the use of industrial solid waste coal gangue as roadbed materials can effectively promote the disposal of large quantities of solid waste coal gangue, solve the dependence of roadbed materials on traditional sand and gravel materials and the land occupation problem caused by coal gangue stacking, and reduce the disturbance of coal gangue to the surrounding ecological environment.
[0003] At present, coal gangue with high calorific value is selected and used for power generation; coal gangue with low calorific value is used as building material or roadbed material; although it is recycled, it is used as roadbed material. The roadbed material has poor compressive strength and the product has poor resistance to chloride ion permeability. The product's compressive strength and chloride ion permeability are difficult to coordinate, and the product has poor antifreeze, heat stability and durability, which limits the product's use efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a roadbed material and method based on coal gangue material to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a method for preparing a roadbed material based on coal gangue material, comprising the following raw materials in parts by weight:
[0007] 75-80 parts of coal gangue, 30-35 parts of silicate cement, 35-40 parts of sand and gravel, 10-15 parts of fly ash with a fineness of 200 mesh, 5-8 parts of limestone, 3-5 parts of sodium carboxymethyl cellulose, 3-5 parts of water reducer, 2-4 parts of citric acid, and 45-50 parts of water; wherein the coal gangue is 2.36-4.75mm coal gangue, 4.75-9.5mm coal gangue, 9.5-19mm coal gangue, and 19-31.5mm coal gangue, which are prepared in a weight ratio of 2.5:1:2.5:1.25.
[0008] Preferably, the sand and gravel material is a mixture of 200-mesh quartz sand and 100-mesh machine-made sand in a weight ratio of 2:1; and the water reducer is a polycarboxylate water reducer.
[0009] Preferably, the roadbed material further comprises 5 to 9 parts of a stabilizing agent and 3 to 5 parts of a modifier based on flaky talc and hybrid glass fiber.
[0010] Preferably, the preparation method of the stabilizing agent is:
[0011] S01: irradiating the nano-bentonite in a proton irradiation box for 5 to 10 minutes at an irradiation power of 350W, and obtaining irradiated nano-bentonite after the irradiation is completed;
[0012] S02: Add 2-5 parts of stearic acid and 1-3 parts of urea to 4-7 parts of 5% chitosan solution and stir to mix well, then add 2-4 parts of sodium dodecylbenzene sulfonate and 1-2 parts of silane coupling agent KH560 to mix well to obtain a regulating solution;
[0013] S03: subjecting the irradiated nano-bentonite and the conditioning liquid to a ball milling conditioning treatment in a weight ratio of 5:3, after the conditioning is completed, washing, filtering, and drying to obtain a conditioned nano-bentonite agent;
[0014] S04: The adjusted nano bentonite agent and the continuity improver are mixed in a weight ratio of 2:5 and ultrasonically treated. After the ultrasonic treatment is completed, the mixture is washed with water, filtered and dried to obtain a stable continuity adjustment agent.
[0015] Preferably, the ball milling speed of the ball milling adjustment treatment is 1000-1500 r / min, and the ball milling is 2 hours; the ultrasonic power of the mixed ultrasonic treatment is 350-400 W, and the ultrasonic time is 20-30 minutes.
[0016] Preferably, the connectivity improver comprises the following raw materials in parts by weight:
[0017] 2 to 5 parts of triisopropanolamine solution, 1 to 3 parts of sodium lignin sulfonate solution, 3 to 5 parts of nano calcium carbonate, 1 to 2 parts of aluminum borate whiskers and 2 to 4 parts of hydroxyapatite.
[0018] Preferably, the mass fraction of the triisopropanolamine solution is 3-5%; the mass fraction of the sodium lignin sulfonate solution is 5-8%.
[0019] Preferably, the preparation method of the modifier based on flaky talc hybrid glass fiber is:
[0020] S101: preheating talcum powder flakes at 55-65° C. for 10-15 minutes, and then immersing in a sufficient amount of 5% by mass sodium silicate solution and stirring, and after stirring, washing, filtering, and drying to obtain talcum powder adjusted with sodium silicate;
[0021] S102: adding glass fibers into a phosphate buffer solution with a pH value of 5.5 at a weight ratio of 2:5 and stirring thoroughly to obtain a glass fiber solution;
[0022] 4-7 parts of glass fiber liquid, 1-3 parts of silane coupling agent KH550, 1-2 parts of nano silica sol and 4-7 parts of 6% by mass yellow dextrin solution are fully mixed to obtain a hybrid glass fiber modified liquid;
[0023] S103: The talc powder adjusted with sodium silicate and the hybrid glass fiber modification liquid are mixed and ball-milled in a weight ratio of (5-7):3, with a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modifier based on flaky talc powder hybrid glass fiber.
[0024] Preferably, the stirring speed of the immersion stirring treatment is 450-500 r / min, and the stirring time is 35-40 min.
[0025] The present invention also provides a method for preparing roadbed materials based on coal gangue materials, comprising the following steps: the raw materials are mixed evenly according to a proportion to obtain the roadbed material of the present invention.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The roadbed material of the present invention adopts coal gangue as the base material, and is matched with sand and gravel, fly ash and limestone to achieve a strengthening effect, while cement and water form the roadbed solidification material; the compressive strength performance of the roadbed material, the coordination of the anti-chloride ion permeability, and the antifreeze and heat stability of the product can be optimized by matching the raw materials, and the stability adjustment and the modifier based on the flaky talcum powder and the hybrid glass fiber are coordinated and matched to enhance the performance together, so that the performance of the product is further improved; the stability adjustment adopts nano-bentonite to be irradiated in a proton irradiation box before, so as to optimize the activity efficiency of the nano-bentonite, and then through stearic acid, Urea was added to a chitosan solution with a mass fraction of 5%, and then sodium dodecylbenzene sulfonate and silane coupling agent KH560 were mixed to obtain a regulating solution. The raw materials in the regulating solution were mixed and coordinated to enhance the interface compatibility of the raw materials by the coordination between chitosan solution, sodium dodecylbenzene sulfonate and silane coupling agent KH560, and the coordination effect of nano-bentonite and the connectivity improver was optimized. The connectivity improver was a mixture of triisopropanolamine solution, sodium lignin sulfonate solution, nano-calcium carbonate, aluminum borate whiskers and hydroxyapatite, and nano-calcium carbonate and aluminum borate whiskers were used as the matrix materials. , using the synergistic effect between the raw materials, using the whisker distribution system of the whisker structure, enhancing the interface connectivity between the raw materials, and using the lamellar bentonite interlaced system, the performance coordination of the product is further improved, and the stability of the product is significantly improved. The modifier based on the flaky talc hybrid glass fiber is preheated at 55-65°C for 10-15min, and then immersed in a sufficient amount of 5% sodium silicate solution by mass and stirred, and the flaky talc is improved with the sodium silicate solution to enhance the stability of the flaky talc interlaced with the reinforced flaky bentonite. In order to further improve the performance of the product, glass fiber is combined with a phosphate buffer solution with a pH value of 5.5 to obtain a glass fiber liquid, and the glass fiber liquid is fully mixed with a silane coupling agent KH550, nano-silica sol and a 6% by mass yellow dextrin solution to obtain a hybrid glass fiber modified liquid. The talc powder adjusted with sodium silicate is ball-milled with the hybrid glass fiber modified liquid, and the system structure is strengthened by the blending and adjustment of the raw materials. At the same time, the raw materials in the hybrid glass fiber modified liquid are coordinated with each other, and the performance of the product system is further enhanced. DETAILED DESCRIPTION
[0028] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] A roadbed material prepared based on coal gangue material in this embodiment includes the following raw materials in parts by weight:
[0030] 75-80 parts of coal gangue, 30-35 parts of Portland cement, 35-40 parts of sand and gravel, 10-15 parts of fly ash with a fineness of 200 mesh, 5-8 parts of limestone, 3-5 parts of sodium carboxymethyl cellulose, 3-5 parts of water reducer, 2-4 parts of citric acid, and 45-50 parts of water; wherein the coal gangue is prepared according to a weight ratio of 2.5:1:2.5:1.25 for coal gangue with a particle size of 2.36-4.75mm, 4.75-9.5mm, 9.5-19mm, and 19-21.5mm.
[0031] The sand and gravel material of this embodiment is a mixture of 200-mesh quartz sand and 100-mesh machine-made sand in a weight ratio of 2:1; the water reducer is a polycarboxylate water reducer.
[0032] The roadbed material of this embodiment also includes 5 to 9 parts of a stability adjuster and 3 to 5 parts of a modifier based on flaky talc and hybrid glass fiber.
[0033] The preparation method of the stabilizing agent of this embodiment is as follows:
[0034] S01: irradiating the nano-bentonite in a proton irradiation box for 5 to 10 minutes at an irradiation power of 350W, and obtaining irradiated nano-bentonite after the irradiation is completed;
[0035] S02: Add 2-5 parts of stearic acid and 1-3 parts of urea to 4-7 parts of 5% chitosan solution and stir to mix well, then add 2-4 parts of sodium dodecylbenzene sulfonate and 1-2 parts of silane coupling agent KH560 to mix well to obtain a regulating solution;
[0036] S03: subjecting the irradiated nano-bentonite and the conditioning liquid to a ball milling conditioning treatment in a weight ratio of 5:3, after the conditioning is completed, washing, filtering, and drying to obtain a conditioned nano-bentonite agent;
[0037] S04: The adjusted nano bentonite agent and the continuity improver are mixed in a weight ratio of 2:5 and ultrasonically treated. After the ultrasonic treatment is completed, the mixture is washed with water, filtered and dried to obtain a stable continuity adjustment agent.
[0038] The ball milling speed of the ball milling adjustment treatment in this embodiment is 1000-1500 r / min, and the ball milling is 2h; the ultrasonic power of the mixed ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.
[0039] The connectivity improver of this embodiment includes the following raw materials in parts by weight:
[0040] 2 to 5 parts of triisopropanolamine solution, 1 to 3 parts of sodium lignin sulfonate solution, 3 to 5 parts of nano calcium carbonate, 1 to 2 parts of aluminum borate whiskers and 2 to 4 parts of hydroxyapatite.
[0041] The mass fraction of the triisopropanolamine solution in this embodiment is 3-5%; the mass fraction of the sodium lignin sulfonate solution is 5-8%.
[0042] The preparation method of the modifier based on flaky talc hybrid glass fiber of this embodiment is:
[0043] S101: preheating talcum powder flakes at 55-65° C. for 10-15 minutes, and then immersing in a sufficient amount of 5% by mass sodium silicate solution and stirring, and after stirring, washing, filtering, and drying to obtain talcum powder adjusted with sodium silicate;
[0044] S102: adding glass fibers into a phosphate buffer solution with a pH value of 5.5 at a weight ratio of 2:5 and stirring thoroughly to obtain a glass fiber solution;
[0045] 4-7 parts of glass fiber liquid, 1-3 parts of silane coupling agent KH550, 1-2 parts of nano silica sol and 4-7 parts of 6% by mass yellow dextrin solution are fully mixed to obtain a hybrid glass fiber modified liquid;
[0046] S103: The talc powder adjusted with sodium silicate and the hybrid glass fiber modification liquid are mixed and ball-milled in a weight ratio of (5-7):3, with a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modifier based on flaky talc powder hybrid glass fiber.
[0047] The stirring speed of the immersion stirring process in this embodiment is 450-500 r / min, and the stirring time is 35-40 min.
[0048] A method for preparing a roadbed material based on coal gangue material in this embodiment includes the following steps: the raw materials are mixed evenly according to a proportion to obtain the roadbed material of the present invention.
[0049] Example 1
[0050] A roadbed material prepared based on coal gangue material in this embodiment includes the following raw materials in parts by weight:
[0051] 75 parts of coal gangue, 30 parts of silicate cement, 35 parts of sand and gravel, 10 parts of fly ash with a fineness of 200 mesh, 5 parts of limestone, 3 parts of sodium carboxymethyl cellulose, 3 parts of water reducer, 2 parts of citric acid, and 45 parts of water; the coal gangue is 2.36mm coal gangue, 4.75mm coal gangue, 9.5mm coal gangue, and 19mm coal gangue, which are prepared in a weight ratio of 2.5:1:2.5:1.25.
[0052] The sand and gravel material of this embodiment is a mixture of 200-mesh quartz sand and 100-mesh machine-made sand in a weight ratio of 2:1; the water reducer is a polycarboxylate water reducer.
[0053] The roadbed material of this embodiment also includes 5 parts of a stability adjuster and 3 parts of a modifier based on flaky talc and hybrid glass fiber.
[0054] The preparation method of the stabilizing agent of this embodiment is as follows:
[0055] S01: irradiating the nano-bentonite in a proton irradiation box for 5 minutes at an irradiation power of 350W, and obtaining irradiated nano-bentonite after the irradiation is completed;
[0056] S02: Add 2 parts of stearic acid and 1 part of urea to 4 parts of 5% chitosan solution and stir to mix well, then add 2 parts of sodium dodecylbenzene sulfonate and 1 part of silane coupling agent KH560 to mix well to obtain a regulating solution;
[0057] S03: subjecting the irradiated nano-bentonite and the conditioning liquid to a ball milling conditioning treatment in a weight ratio of 5:3, after the conditioning is completed, washing, filtering, and drying to obtain a conditioned nano-bentonite agent;
[0058] S04: The adjusted nano bentonite agent and the continuity improver are mixed in a weight ratio of 2:5 and ultrasonically treated. After the ultrasonic treatment is completed, the mixture is washed with water, filtered and dried to obtain a stable continuity adjustment agent.
[0059] The ball milling speed of the ball milling adjustment treatment in this embodiment is 1000 r / min, and the ball milling is 2 hours; the ultrasonic power of the mixed ultrasonic treatment is 350 W, and the ultrasonic time is 20 minutes.
[0060] The connectivity improver of this embodiment includes the following raw materials in parts by weight:
[0061] 2 parts of triisopropanolamine solution, 1 part of sodium lignin sulfonate solution, 3 parts of nano calcium carbonate, 1 part of aluminum borate whisker and 2 parts of hydroxyapatite.
[0062] The mass fraction of the triisopropanolamine solution in this embodiment is 3%; the mass fraction of the sodium lignin sulfonate solution is 5%.
[0063] The preparation method of the modifier based on flaky talc hybrid glass fiber of this embodiment is:
[0064] S101: preheating flaky talc at 55° C. for 10 min, then immersing in a sufficient amount of 5% by mass sodium silicate solution and stirring, and after stirring, washing, filtering, and drying to obtain talc adjusted with sodium silicate;
[0065] S102: adding glass fibers into a phosphate buffer solution with a pH value of 5.5 at a weight ratio of 2:5 and stirring thoroughly to obtain a glass fiber solution;
[0066] 4 parts of glass fiber liquid, 1 part of silane coupling agent KH550, 1 part of nano silica sol and 4 parts of 6% by mass yellow dextrin solution were fully mixed to obtain a hybrid glass fiber modified liquid;
[0067] S103: The talc powder adjusted with sodium silicate and the hybrid glass fiber modification liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modifier based on flaky talc powder and hybrid glass fiber.
[0068] The stirring speed of the immersion stirring process in this embodiment is 450 r / min, and the stirring time is 35 min.
[0069] A method for preparing a roadbed material based on coal gangue material in this embodiment includes the following steps: the raw materials are mixed evenly according to a proportion to obtain the roadbed material of the present invention.
[0070] Example 2
[0071] A roadbed material prepared based on coal gangue material in this embodiment includes the following raw materials in parts by weight:
[0072] 80 parts of coal gangue, 35 parts of silicate cement, 40 parts of sand and gravel, 15 parts of fly ash with a fineness of 200 mesh, 8 parts of limestone, 5 parts of sodium carboxymethyl cellulose, 5 parts of water reducer, 4 parts of citric acid, and 50 parts of water; the coal gangue is 4.75mm coal gangue, 9.5mm coal gangue, 19mm coal gangue, and 21.5mm coal gangue, which are prepared in a weight ratio of 2.5:1:2.5:1.25.
[0073] The sand and gravel material of this embodiment is a mixture of 200-mesh quartz sand and 100-mesh machine-made sand in a weight ratio of 2:1; the water reducer is a polycarboxylate water reducer.
[0074] The roadbed material of this embodiment also includes 9 parts of a stability adjuster and 5 parts of a modifier based on flaky talc and hybrid glass fiber.
[0075] The preparation method of the stabilizing agent of this embodiment is as follows:
[0076] S01: irradiating the nano-bentonite in a proton irradiation box for 10 minutes at an irradiation power of 350W, and obtaining irradiated nano-bentonite after the irradiation is completed;
[0077] S02: Add 5 parts of stearic acid and 3 parts of urea to 7 parts of 5% chitosan solution and stir to mix well, then add 4 parts of sodium dodecylbenzene sulfonate and 2 parts of silane coupling agent KH560 to mix well to obtain a regulating solution;
[0078] S03: subjecting the irradiated nano-bentonite and the conditioning liquid to a ball milling conditioning treatment in a weight ratio of 5:3, after the conditioning is completed, washing, filtering, and drying to obtain a conditioned nano-bentonite agent;
[0079] S04: The adjusted nano bentonite agent and the continuity improver are mixed in a weight ratio of 2:5 and ultrasonically treated. After the ultrasonic treatment is completed, the mixture is washed with water, filtered and dried to obtain a stable continuity adjustment agent.
[0080] The ball milling speed of the ball milling adjustment treatment in this embodiment is 1500r / min, and the ball milling is 2h; the ultrasonic power of the mixed ultrasonic treatment is 400W, and the ultrasonic time is 30min.
[0081] The connectivity improver of this embodiment includes the following raw materials in parts by weight:
[0082] 5 parts of triisopropanolamine solution, 3 parts of sodium lignin sulfonate solution, 5 parts of nano calcium carbonate, 2 parts of aluminum borate whiskers and 4 parts of hydroxyapatite.
[0083] The mass fraction of the triisopropanolamine solution in this embodiment is 5%; the mass fraction of the sodium lignin sulfonate solution is 8%.
[0084] The preparation method of the modifier based on flaky talc hybrid glass fiber of this embodiment is:
[0085] S101: preheating flaky talc at 65° C. for 15 min, then immersing in a sufficient amount of 5% by mass sodium silicate solution and stirring, and after stirring, washing, filtering, and drying to obtain talc adjusted with sodium silicate;
[0086] S102: adding glass fibers into a phosphate buffer solution with a pH value of 5.5 at a weight ratio of 2:5 and stirring thoroughly to obtain a glass fiber solution;
[0087] 7 parts of glass fiber liquid, 3 parts of silane coupling agent KH550, 2 parts of nano silica sol and 7 parts of 6% by mass yellow dextrin solution were fully mixed to obtain a hybrid glass fiber modified liquid;
[0088] S103: The talc powder adjusted with sodium silicate and the hybrid glass fiber modification liquid are mixed in a weight ratio of 7:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modifier based on flaky talc powder and hybrid glass fiber.
[0089] The stirring speed of the immersion stirring process in this embodiment is 500 r / min, and the stirring time is 40 min.
[0090] A method for preparing a roadbed material based on coal gangue material in this embodiment includes the following steps: the raw materials are mixed evenly according to a proportion to obtain the roadbed material of the present invention.
[0091] Example 3
[0092] A roadbed material prepared based on coal gangue material in this embodiment includes the following raw materials in parts by weight:
[0093] 78.5 parts of coal gangue, 32.5 parts of Portland cement, 37.5 parts of sand and gravel, 12.5 parts of fly ash with a fineness of 200 mesh, 6.5 parts of limestone, 4 parts of sodium carboxymethyl cellulose, 4 parts of water reducer, 3 parts of citric acid, and 47.5 parts of water; the coal gangue is 4.75mm coal gangue, 9.5mm coal gangue, 19mm coal gangue, and 21.5mm coal gangue, which are prepared in a weight ratio of 2.5:1:2.5:1.25.
[0094] The sand and gravel material of this embodiment is a mixture of 200-mesh quartz sand and 100-mesh machine-made sand in a weight ratio of 2:1; the water reducer is a polycarboxylate water reducer.
[0095] The roadbed material of this embodiment also includes 7 parts of a stability adjuster and 4 parts of a modifier based on flaky talc and hybrid glass fiber.
[0096] The preparation method of the stabilizing agent of this embodiment is as follows:
[0097] S01: irradiating the nano-bentonite in a proton irradiation box for 7.5 minutes at an irradiation power of 350W, and obtaining irradiated nano-bentonite after the irradiation is completed;
[0098] S02: Add 3.5 parts of stearic acid and 2 parts of urea to 5.5 parts of 5% chitosan solution and stir to mix well, then add 3 parts of sodium dodecylbenzene sulfonate and 1.5 parts of silane coupling agent KH560 to mix well to obtain a regulating solution;
[0099] S03: subjecting the irradiated nano-bentonite and the conditioning liquid to a ball milling conditioning treatment in a weight ratio of 5:3, after the conditioning is completed, washing, filtering, and drying to obtain a conditioned nano-bentonite agent;
[0100] S04: The adjusted nano bentonite agent and the continuity improver are mixed in a weight ratio of 2:5 and ultrasonically treated. After the ultrasonic treatment is completed, the mixture is washed with water, filtered and dried to obtain a stable continuity adjustment agent.
[0101] The ball milling speed of the ball milling adjustment treatment in this embodiment is 1250 r / min, and the ball milling is 2 hours; the ultrasonic power of the mixed ultrasonic treatment is 370 W, and the ultrasonic time is 25 minutes.
[0102] The connectivity improver of this embodiment includes the following raw materials in parts by weight:
[0103] 3.5 parts of triisopropanolamine solution, 2 parts of sodium lignin sulfonate solution, 4 parts of nano calcium carbonate, 1.5 parts of aluminum borate whiskers and 3 parts of hydroxyapatite.
[0104] The mass fraction of the triisopropanolamine solution in this embodiment is 4%; the mass fraction of the sodium lignin sulfonate solution is 6.5%.
[0105] The preparation method of the modifier based on flaky talc hybrid glass fiber of this embodiment is:
[0106] S101: preheating talcum powder flakes at 60° C. for 12.5 min, then immersing in a sufficient amount of 5% by mass sodium silicate solution and stirring, and after stirring, washing, filtering, and drying to obtain talcum powder adjusted with sodium silicate;
[0107] S102: adding glass fibers into a phosphate buffer solution with a pH value of 5.5 at a weight ratio of 2:5 and stirring thoroughly to obtain a glass fiber solution;
[0108] 5.5 parts of glass fiber liquid, 2 parts of silane coupling agent KH550, 1.5 parts of nano silica sol and 5.5 parts of 6% by mass yellow dextrin solution were fully mixed to obtain a hybrid glass fiber modified liquid;
[0109] S103: The talcum powder adjusted with sodium silicate and the hybrid glass fiber modification liquid are mixed in a weight ratio of 2:1 and ball-milled at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a modifier based on flaky talcum powder hybrid glass fiber.
[0110] The stirring speed of the immersion stirring process in this embodiment is 475 r / min, and the stirring time is 37.5 min.
[0111] A method for preparing a roadbed material based on coal gangue material in this embodiment includes the following steps: the raw materials are mixed evenly according to a proportion to obtain the roadbed material of the present invention.
[0112] Comparative Example 1
[0113] The difference from Example 3 is that no stabilizing agent is added.
[0114] Comparative Example 2
[0115] The difference from Example 3 is that no regulating liquid treatment is used in the preparation of the stabilizing agent.
[0116] Comparative Example 3
[0117] The difference from Example 3 is that the preparation method of the regulating solution is different:
[0118] 3.5 parts of stearic acid were added to 5.5 parts of deionized water and stirred to mix well, and then 3 parts of sodium dodecylbenzene sulfonate were added and mixed thoroughly to obtain a regulating solution.
[0119] Comparative Example 4
[0120] The difference from Example 3 is that no continuity improver was used in the preparation of the stability adjustment agent.
[0121] Comparative Example 5
[0122] The difference from Example 3 is that no modifier based on flaky talc hybrid glass fiber is added.
[0123] Comparative Example 6
[0124] The difference from Example 3 is that no talc agent adjusted by sodium silicate was added in the preparation of the modifier based on flaky talc and hybrid glass fiber.
[0125] Comparative Example 7
[0126] The difference from Example 3 is that no hybrid glass fiber modifying liquid is added in the preparation of the modifier based on flaky talc hybrid glass fiber.
[0127] Comparative Example 8
[0128] The difference from Example 3 is that no glass fiber liquid is added in the preparation of the hybrid glass fiber modified liquid.
[0129] Comparative Example 9
[0130] The difference from Example 3 is that no nano-silica sol and yellow dextrin solution are added in the preparation of the hybrid glass fiber modified liquid.
[0131] The products of Examples 1-3 and Comparative Examples 1-9 were tested for compressive strength and chloride ion permeability resistance under normal conditions, and the products were placed at -10°C for 12 hours, and then transferred to 60°C for 12 hours, and the test was repeated 10 times to test the antifreeze and heat resistance of the products. The products of Examples 1-3 and Comparative Examples 1-9 were made into cylindrical samples with a diameter of 100 mm and a height of 50 mm, and were immersed in 10% sodium chloride solution for 200 days. The electric flux of the products was tested for 6 hours, and the performance measurement results are as follows;
[0132]
[0133] It can be concluded from Examples 1-3 and Comparative Examples 1-9 that the product of Example 3 of the present invention has excellent compressive strength and chloride ion permeability resistance under normal conditions, and the product performance can be coordinated and improved. At the same time, it still has excellent performance stability under antifreeze and heat resistance conditions;
[0134] From Comparative Examples 1-9 and Example 3, it can be seen that the product does not add a stabilizing agent and does not add one of the modifiers based on flaky talc and hybrid glass fiber, and the performance of the product deteriorates significantly. The performance effect of the product is most significant when the two are coordinated and enhanced together.
[0135] The performance of the products tended to deteriorate when the adjusting liquid was not used in the preparation of the stability adjustment, the adjusting liquid preparation method was different, and the continuity improver was not used in the preparation of the stability adjustment. The performance effect of the products obtained by different methods was the most significant. At the same time, the performance change trend of the products was more obvious when the continuity improver was not used in the preparation of the continuity adjustment.
[0136] The performance of the products tended to deteriorate when no talc powder adjusted with sodium silicate was added in the preparation of the modifier based on flaky talc and hybrid glass fiber, no hybrid glass fiber modifying liquid was added in the preparation of the modifier based on flaky talc and hybrid glass fiber, no glass fiber liquid was added in the preparation of the hybrid glass fiber modifying liquid, and no nano-silica sol and yellow dextrin solution were added in the preparation of the hybrid glass fiber modifying liquid. Only when the hybrid glass fiber modifying liquid obtained by the method of the present invention was treated with the talc powder adjusted with sodium silicate of the present invention, the performance effect of the product was the most significant. Other methods were not as obvious as the effect of the present invention.
[0137] Since the connectivity improver has a significant impact on the performance of the product, further research is needed:
[0138] Experimental Example 1
[0139] The only difference from the embodiment is that no triisopropanolamine solution is added to the connectivity improver.
[0140] Experimental Example 2
[0141] The only difference from the embodiment is that no sodium lignin sulfonate solution is added to the connectivity improver.
[0142] Experimental Example 3
[0143] The only difference from the embodiment is that no nano calcium carbonate is added to the connectivity improver.
[0144] Experimental Example 4
[0145] The only difference from the embodiment is that no aluminum borate whiskers are added to the connectivity improver.
[0146] Experimental Example 5
[0147] The only difference from the example is that hydroxyapatite is not added to the connectivity improver.
[0148]
[0149] It can be seen from Experimental Examples 1-5 that when nano calcium carbonate is not added to the connectivity improver, the performance of the product tends to deteriorate significantly, followed by when aluminum borate whiskers are not added. At the same time, when triisopropanolamine solution, sodium lignin sulfonate solution and hydroxyapatite are not added to the connectivity improver, the performance of the product tends to deteriorate to varying degrees. The performance effect of the product is most significant when the specific raw materials of the present invention are used. The effects of other raw materials are not as obvious as those of the present invention.
[0150] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0151] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing roadbed materials based on coal gangue materials, characterized in that: The invention comprises the following raw materials in parts by weight: 75-80 parts of coal gangue, 30-35 parts of silicate cement, 35-40 parts of sand and gravel, 10-15 parts of fly ash with a fineness of 200 mesh, 5-8 parts of limestone, 3-5 parts of sodium carboxymethyl cellulose, 3-5 parts of water reducing agent, 2-4 parts of citric acid, and 45-50 parts of water; The coal gangue is prepared by mixing 2.36-4.75 mm coal gangue, 4.75-9.5 mm coal gangue, 9.5-19 mm coal gangue and 19-31.5 mm coal gangue in a weight ratio of 2.5:1:2.5:1.25; The roadbed material also includes 5 to 9 parts of a stabilizing agent and 3 to 5 parts of a modifier based on flaky talc and hybrid glass fiber; The preparation method of the modifier based on flaky talc hybrid glass fiber is as follows: S101: preheating talcum powder flakes at 55-65° C. for 10-15 minutes, and then immersing in a sufficient amount of 5% by mass sodium silicate solution and stirring, and after stirring, washing, filtering, and drying to obtain talcum powder adjusted with sodium silicate; S102: adding glass fibers into a phosphate buffer solution with a pH value of 5.5 at a weight ratio of 2:5 and stirring thoroughly to obtain a glass fiber solution; 4-7 parts of glass fiber liquid, 1-3 parts of silane coupling agent KH550, 1-2 parts of nano silica sol and 4-7 parts of 6% by mass yellow dextrin solution are fully mixed to obtain a hybrid glass fiber modified liquid; S103: the talc powder adjusted with sodium silicate and the hybrid glass fiber modification liquid are mixed and ball-milled in a weight ratio of (5-7):3, the ball milling speed is 1500r / min, the ball milling is performed for 2h, and after the ball milling is completed, the mixture is washed with water and dried to obtain a modifier based on flaky talc powder hybrid glass fiber; The preparation method of the stabilizing agent is as follows: S01: irradiating the nano-bentonite in a proton irradiation box for 5 to 10 minutes at an irradiation power of 350W, and obtaining irradiated nano-bentonite after the irradiation is completed; S02: Add 2-5 parts of stearic acid and 1-3 parts of urea to 4-7 parts of 5% chitosan solution and stir to mix well, then add 2-4 parts of sodium dodecylbenzene sulfonate and 1-2 parts of silane coupling agent KH560 to mix well to obtain a regulating solution; S03: subjecting the irradiated nano-bentonite and the conditioning liquid to a ball milling conditioning treatment in a weight ratio of 5:3, after the conditioning is completed, washing, filtering, and drying to obtain a conditioned nano-bentonite agent; S04: The adjusted nano bentonite agent and the continuity improver are mixed and ultrasonically treated in a weight ratio of 2:
5. After the ultrasonic treatment is completed, the mixture is washed with water, filtered and dried to obtain a stable continuity agent; The connectivity improver comprises the following raw materials in parts by weight: 2 to 5 parts of triisopropanolamine solution, 1 to 3 parts of sodium lignin sulfonate solution, 3 to 5 parts of nano calcium carbonate, 1 to 2 parts of aluminum borate whiskers and 2 to 4 parts of hydroxyapatite.
2. The method for preparing roadbed material based on coal gangue material according to claim 1, characterized in that: The sand and gravel are a mixture of 200-mesh quartz sand and 100-mesh machine-made sand in a weight ratio of 2:1; the water reducer is a polycarboxylate water reducer.
3. The method for preparing roadbed material based on coal gangue material according to claim 1, characterized in that: The ball milling speed of the ball milling adjustment treatment is 1000-1500 r / min, and the ball milling is 2 hours; the ultrasonic power of the mixed ultrasonic treatment is 350-400 W, and the ultrasonic time is 20-30 minutes.
4. The method for preparing roadbed material based on coal gangue material according to claim 1, characterized in that: The mass fraction of the triisopropanolamine solution is 3-5%; the mass fraction of the sodium lignin sulfonate solution is 5-8%.
5. The method for preparing roadbed material based on coal gangue material according to claim 1, characterized in that: The stirring speed of the immersion stirring treatment is 450-500 r / min, and the stirring time is 35-40 min.
6. A method for preparing roadbed materials based on coal gangue materials as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: The roadbed material can be obtained by mixing the raw materials uniformly according to the proportion.
Citation Information
Patent Citations
Cement mortar prepared from coal gangue material and preparation method thereof
CN118459177A
Cited By
Composite solidifying agent modified fly ash-gangue subgrade material and preparation method thereof
CN122878104A